2015
DOI: 10.3389/fmicb.2015.00960
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of virus occurrence in two freshwater lakes captured through metagenomic analysis

Abstract: Viruses are the most abundant microorganisms in the aquatic environment, yet the identification of viruses and assessing their diversity still remains a challenge. Here, we present a robust, routinely usable approach to identify viruses from two freshwater lakes of the lower Great Lakes region, Lake Ontario, and Lake Erie. We collected water samples from six different beaches of these two lakes during the summer period of 2012 and 2013, and separated into three distinct fractions, namely a bacterial fraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 53 publications
3
59
1
Order By: Relevance
“…In this geospatial metagenomics study, we identified virome abundance and diversity in different reservoirs and tributaries. Due to insufficient viral genome sequencing information in the NCBI, 41.4% of the virome genome had no significant hits and bacteriophages were the most abundant organisms in the matrix, which is in agreement with previous studies of surface water viromes (Mohiuddin and Schellhorn, 2015;Skvortsov et al, 2016;Tseng et al, 2013). Phages, considered to be the most abundant and diverse biological entities on Earth, play an important role in shaping biological and geochemical processes at the global scale (Díaz-Muñoz and Koskella, 2014).…”
Section: Geospatial Distribution Of Viromesupporting
confidence: 87%
“…In this geospatial metagenomics study, we identified virome abundance and diversity in different reservoirs and tributaries. Due to insufficient viral genome sequencing information in the NCBI, 41.4% of the virome genome had no significant hits and bacteriophages were the most abundant organisms in the matrix, which is in agreement with previous studies of surface water viromes (Mohiuddin and Schellhorn, 2015;Skvortsov et al, 2016;Tseng et al, 2013). Phages, considered to be the most abundant and diverse biological entities on Earth, play an important role in shaping biological and geochemical processes at the global scale (Díaz-Muñoz and Koskella, 2014).…”
Section: Geospatial Distribution Of Viromesupporting
confidence: 87%
“…Nucleic acids were isolated from the collected samples in the amount of 2.5-4 lg per 1 L water sample, which corresponds to the average number of isolated nucleic acids from the same volume [29]. Considering that rather small input amounts of ng are sufficient for sequencing of nucleic acid with Illumina HiSeq [30], in further studies it will be possible to reduce the volume of water samples in order to decrease the time and cost of isolation of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, virus-focused metagenomics studies either concentrate virus-genomes via their virions or enrich for double-stranded RNA that is a broadly shared feature of virus replication. The virus-enriched nucleic acids are then sequenced by shotgun metagenomics methods (Bibby 2013) for the detection of viruses in environmental material, including marine water (Schmidt et al 2014), fresh water (Mohiuddin & Schellhorn 2015), soil (Ballaud et al 2016), crop plants (Aw et al 2016), native plants and weed plant species (Blouin et al 2016). We remain unable to recommend a single molecular approach to comprehensively target all of the diversity of viral material for metabarcoding studies in an unbiased manner, i.e.…”
Section: Recommendationmentioning
confidence: 99%